1998
DOI: 10.2337/diacare.21.7.1058
|View full text |Cite
|
Sign up to set email alerts
|

An Asian Multicenter Clinical Trial to Assess the Efficacy and Tolerability of Acarbose Compared With Placebo in Type 2 Diabetic Patients Previously Treated With Diet

Abstract: In this multicenter study involving six ethnic groups, acarbose 100 mg t.i.d. was an effective, safe, and generally well-tolerated therapy in Asian type 2 diabetic patients with dietary failure. In some patients with troublesome gastrointestinal symptoms, a lower dosage may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Could the results obtained with voglibose in Japanese patients be extrapolated to other populations, in view of the well known good efficacy and safety profile of α-glucosidase inhibitors in Asians? 18 The answer might be yes because the reported results agree with those of the STOP-NIDDM trial with acarbose in Canadians and Europeans. 6 With the positive results obtained with metformin 1,8,12 and α-glucosidase inhibitors (today's study and references 8 and 19) on the one hand, and the rather high residual risk of developing type 2 diabetes with monotherapy on the other, treatment with a combination of the two types of drugs might be an option.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Could the results obtained with voglibose in Japanese patients be extrapolated to other populations, in view of the well known good efficacy and safety profile of α-glucosidase inhibitors in Asians? 18 The answer might be yes because the reported results agree with those of the STOP-NIDDM trial with acarbose in Canadians and Europeans. 6 With the positive results obtained with metformin 1,8,12 and α-glucosidase inhibitors (today's study and references 8 and 19) on the one hand, and the rather high residual risk of developing type 2 diabetes with monotherapy on the other, treatment with a combination of the two types of drugs might be an option.…”
mentioning
confidence: 50%
“…16 α-glucosidase inhibitors seem to exert a good glucose-lowering effect (with an acceptable gastrointestinal tolerance) in Asian people, presumably because of specific food habits. 18 Therefore the results of the trial by Kawamori and colleagues in The Lancet today, in which the effect of voglibose (another α-glucosidase inhibitor) was assessed in Japanese patients with impaired glucose tolerance, raise much interest. 5 Analysis after almost 50 weeks of treatment showed that voglibose (0 .…”
mentioning
confidence: 99%
“…Therefore, patients with dapagliflozin may have better medication adherence and fewer therapy discontinuations as compared with acarbose in some extent. In this study, according to the reports of included RCTs, therapy discontinuation rates were 8.6% and 14.6% in dapagliflozin and acarbose treatment, respectively, with reasons such as intolerance to therapy or adverse events, lost to follow-up, poor glycaemic control, poor medication adherence, or no longer met study criteria [41][42][43][55][56]. Potential better therapy adherence may be another advantage of dapagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…Title and abstract screening resulted in 52 papers for detailed review. After examination of full-text articles, four eligible studies were finally included in the meta-analysis (two on dapagliflozin versus placebo, and two on acarbose versus placebo) [41][42][55][56] (Fig 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• an important manifestation in the early course of type 2 diabetes mellitus (T2DM) • a critical target for achieving glycemic control • a contributing factor in the pathogenesis of cardiovascular disease -Acarbose indirectly optimizes glucose metabolism during the day through adaptation of insulin secretion 2 • Numerous studies have shown beneficial effects of acarbose as a 1st-, 2nd-and 3rd-line treatment option, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] for which it is recommended by both the International Diabetes Federation (IDF) and American Association for Clinical Endocrinologists (AACE) 29,30 • However, prescribing of acarbose varies around the world due to a perception that efficacy is limited in some ethnic and regional groups • We therefore analyzed pooled data from acarbose post-marketing studies (PMS) and non-interventional studies (NIS) to examine whether differences between patients of European Caucasian and Asian ethnicity exist based on a large body of evidence…”
Section: Introductionmentioning
confidence: 99%